Chatbot AI Riau tourism towards society 5.0 success - Melia Vivi Ningrum; Sayyidina Anshari Ahmad; M Abyan Belantara; M Dafa Al-Sa’ban; Qistan Alif Santana; Rahmat Alfitri; Okfalisa Okfalisa (Lembaga Studi Pendidikan dan Rekayasa Alam Riau, 2024)
Riau Province stands out as one of the most rapidly developing regions in Indonesia, showcasing significant advancements economy, population, and tourism. The strategic positioning of Riau Province along the world's busiest routes, establishes this province as a focal point for diverse activities from multiple nations. Furthermore, the natural resources of Riau Province provide it as a significant business hub by substantial activities. This undoubtedly impacts the cross section both business and tourist visitors from local and international. Unfortunately, it is found that information pertaining to Riau tourism is under-addressed the visitors’ need. Therefore, the chatbot artificial intelligent (AI) is developed to deliver comprehensive information about tourism in Riau, encompassing tourist attractions, culinary, and merchandise destinations. This chatbot is adopted a prototyping approach for software development with natural language processing, employing tools such as Xampp, Visual Studio Code, PHP for programming language, and the Botman for the library. This chatbot is then integrated with a customized website platform utilizing an accessible API. The questions are derived from commonly asked questions on the tourism platform, limited into five tourist attractions, culinary options, or merchandise’s spot. To evaluate, a black-box and user acceptance testing techniques will be employed to verify that the application operates as intended and receives favorable feedback from users. This chatbot grows into the smart and responsive tool tailored to tourism needs in Riau. This tool supports the Society 5.0 that concerns on human centric, technology, and resilience social and community while preserving the cultural elements of Riau’s Malay heritage.